Urban linkages in relation to the effectiveness of urban space from the aspect of connectivity : a case study of pedestrian linkages proposal by KLSP 2020 - 410518 Siti Marsitah Rosly (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2007